Monitoring immune responses in the tumor microenvironment. (August 2016) - Wargo, Jennifer A; Reddy, Sangeetha M; Reuben, Alexandre; Sharma, Padmanee
Highlights: Fresh tissue is more reliable for immune monitoring than archival tissue. Pre-surgical trials are important for adequate tissue collection. Immune system is dynamic, and longitudinal monitoring on therapy is needed. 'Hot' and 'cold' tumors show different pathophysiology and treatment responses. High dimensional single cell profiling highlights extensive immune heterogeneity. Abstract : Immune monitoring in the tumor microenvironment allows for important insights into immune mechanisms of response and resistance to various cancer treatments; however clinical challenges exist using current strategies. Significant questions remain regarding monitoring of archival versus fresh tissue, assessment of static versus dynamic markers, evaluation of limited tissue samples, and the translation of insights gained from immunologically 'hot' tumors such as melanoma to other 'cold' tumor microenvironments prevalent in other cancer types. Current and emerging immune monitoring strategies will be examined herein, and genomic-based assays complementing these techniques will also be discussed. Finally, host genomic and external environmental factors influencing anti-tumor immune responses will be considered, including the role of the gut microbiome. Though optimal immune monitoring techniques are in evolution, great promise exists in recent advances that will help guide patient selection as far as type, sequence, and combination of therapeutic regimens to enhance anti-tumor immunity and clinical responses.